STRATEGI PEMERATAAN EKONOMI RAKYAT YANG BERKEADILAN - Ketut Rendi Astuti (Forum Manajemen, 2018)
In order to accelarate uquity economic and equitable hence the government should buil infrastructure in all line. So that to make good and service distribution line become easy and cheaper, so that small public can enjoytecnology advance. The government effort to overcome economic gap by release economic policy which equitable and focut on three things as follows: 1) by giving road acces, 2) opportunity freely, 3) improvement on human resource capacity. Small enterprise should empowered and each regency should there is a entrepreneur who have equitable commitment, so that growth which equitable become guidelles to empowering of public so that don’t occure economic gap.